2012
DOI: 10.1590/s0004-282x2012000300012
|View full text |Cite
|
Sign up to set email alerts
|

Aquaporin 9 in rat brain after severe traumatic brain injury

Abstract: Predominantly caused by motor vehicle accidents, the traumatic brain injury (TBI) is the leading cause of death and severe disability among people under the age of 45 in Western industrialized countries 1 . Almost all patients suffer from severe disorder of energy metabolism 2 , ionic dysfunction 3 , and water homeostasis 4 after TBI. Experimental evidences indicate that aquaporin 9 (AQP9), which is one member of the water channel family in brain, can facilitate the flow of water and permeate glycerol, monocar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 16 publications
1
15
0
Order By: Relevance
“…We found the expression of Kcnj10 (encoding the Kir4.1 channel) in the EGFP + cells to be rather constant, while higher levels of Kcnj16 (encoding Kir5.1) transcripts were found in cells from subpopulations A1 and A3. We did not see any correlation between Aqp4 and Kcnj10 expression on the cellular level in any of the subpopulations in agreement with previous data showing the lack of any direct interaction between Kir4.1 and AQP4 [46], [47] and their different regulations of expression [48]. In agreement with recent findings [25], [49] we showed that EGFP + mature cortical astrocytes from P30 and P50 (comprising the B3 subpopulation) express low levels of Grm5, as a result of a significant decrease in Grm5 expression towards astrocytic maturation, and a high level of Grm3.…”
Section: Discussionsupporting
confidence: 92%
“…We found the expression of Kcnj10 (encoding the Kir4.1 channel) in the EGFP + cells to be rather constant, while higher levels of Kcnj16 (encoding Kir5.1) transcripts were found in cells from subpopulations A1 and A3. We did not see any correlation between Aqp4 and Kcnj10 expression on the cellular level in any of the subpopulations in agreement with previous data showing the lack of any direct interaction between Kir4.1 and AQP4 [46], [47] and their different regulations of expression [48]. In agreement with recent findings [25], [49] we showed that EGFP + mature cortical astrocytes from P30 and P50 (comprising the B3 subpopulation) express low levels of Grm5, as a result of a significant decrease in Grm5 expression towards astrocytic maturation, and a high level of Grm3.…”
Section: Discussionsupporting
confidence: 92%
“…One study [30] also found that hypertonicity affected AQP4, but not AQP1 expression, suggesting that AQP1 and AQP4 expression is regulated by different mechanisms. Several studies have shown that acute brain injuries, including ICH, ischemic stroke, and brain trauma, alter AQP4 and AQP9 expression, and that decreased expression or gene knockout of AQP4 and AQP9 ameliorates brain edema and neurological deficits [10,[20][21][22][23][24][25]31] . The level and duration of AQP4 expression was temporally correlated with the degree of brain edema in a middle cerebral artery (MCA) occlusion model.…”
Section: Discussionmentioning
confidence: 99%
“…AQP9 is not only a water channel; it also facilitates the transfer of several solutes, including glycerol, urea, and monocarboxylate, suggesting that it plays an additional role in energy metabolism [17] . Many studies have shown that AQP1, AQP4 and AQP9 are associated with cerebral edema induced by several types of brain injury, including ICH, subarachnoid hemorrhage, ischemic stroke and brain trauma [10,[20][21][22][23][24][25][26] . However, the relationship between curcumin and AQPs has not been studied in ICH.…”
Section: Introductionmentioning
confidence: 99%
“…42 Aquaporins, matrix metalloproteinases, inflammatory mediators, and oxidative stress have all been implicated in the development of the cytotoxic cerebral edema that occurs after TBI. 8,11,[43][44][45][46][47][48] It would be reasonable to think that MLCK plays a role in the development of cytotoxic edema as well as vasogenic edema. The common thread between each of these mechanisms and MLCK is calcium calmodulin; however, how MLCK interacts with any of these pathways after TBI has yet to be determined.…”
Section: Discussionmentioning
confidence: 99%